WOMEN WRITE BACK: ALTERNATIVE LEGAL RHETORICS IN INCHBALD, WOLLSTONECRAFT AND OPIE. Issue 1 (2nd January 2016) - Wallace, Miriam L.
ABSTRACT: This essay examines three scenes that engage legal situations and rhetoric by the reformist British women writers Elizabeth Inchbald, Mary Wollstonecraft and Amelia Alderson Opie. Staging legal trials in which women speak or intervene through writing, each critiques English legal conventions that were under particular pressure in the late 1700s and early 1800s. Inchbald, in Nature and Art, turns to the language of sensibility and mutual obligation, casting legal authorities as inauthentic actors by staging a trial in which only the suffering woman is punished; the guilty male judge realizes his complicity only when it is too late. Wollstonecraft, in The Wrongs of Woman, uses a language of rational agency that appeals to pathos and ethos to contest a juridical setting which excludes the wife's account and values one set of passions while eliding others. Opie, in the final section of her moral treatise Illustrations of Lying, in All Its Branches, invokes the language of religious piety to critique institutionalized legal figures and practices, rewriting a case of child murder before Justice William Hale from a prior century. Each proposes a relational and ethical form of speech that depends on a presumed metaphysics of presence embodied in female writing; in so doing, each invites women and women readers to engage in debating the goals and practices of English law.